Sistem Manajemen Cafe dan Resto Berbasis Web dengan Framework Codeigniter dan MySql - Setiadi, David (Infoman's, 2019)
The café and restaurant management system is built to know the restaurant-restaurant or cafe-cafe business process by utilizing or using a smart restaurant system. The method used in this study is the waterfall method. Research shows that utilizing a restaurant's smart application can provide convenience in transacting some of which are useful for small to mid-sized restaurant / cafe management which can be used to record waiter menus and cashiers for sales transactions. Ease in recording financial statements, income statement and accounts receivable. Time-effective and efficient transactions in the use of paper for paper (papperless); Recording of cash out and payroll employees